تطبيق تعليم النحو لفهم مادة اللغة العربية لطلاب فصل الحادي عشر بالمدرسة العالية الحكومية 10 جومبانج - Fitrawan, Tomi; Arif Setyabudi, Muhammad (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2024)
This study investigates the application of Arabic grammar teaching to enhance the understanding of Arabic subjects among 11th-grade students at SMAN 10 Jombang. The research employs a qualitative method with a descriptive-analytical approach, using direct observation, interviews, and documentation for data collection. The results show that the grammar teaching implementation includes objectives, methods, media, and evaluations. The objective is to facilitate students' understanding of Arabic grammar rules. The standard or deductive method, which first presents grammar rules followed by examples, is used. Media such as blackboards, YouTube, learning formats created by the grammar teacher, and projectors are utilized. The advantages of this approach include better comprehension of grammar rules, quick understanding of material, increased vocabulary, and additional enrichment materials to facilitate learning Arabic.